Disruption at the Door - A Taxonomy on Subscription Models in Retailing - Thomas Rudolph; Severin Friedrich Bischof; Tim Böttger; Natalie Weiler (Marketing Review St.Gallen, 2017)
Subscription models have become a popular new way for consumers to do their shopping. This paper presents a taxonomy of the three main archetypes of subscription models and develops a classification scheme with type-specific features relevant to their successful management. An implementation framework offers managers a guideline to introduce subscription models of their own.
Keywords: 650